Case Report: Traumatic Stress and Developmental Regression: An Unintended Consequence of Complex Cardiac Care - Dahl, Claire M.; Kroupina, Maria; Said, Sameh M.; Somani, Arif (Frontiers in Pediatrics, 2021)
This brief case report outlines a novel approach to supporting the development of a pediatric complex cardiac care patient. Patient P is a 19-month old patient who spent 5.5 months in hospital and underwent multiple surgeries including heart transplantation. This case report explores the impacts of his condition and care on his development and family functioning within the framework of an integrated care model. This case report is uniquely complimented by outpatient neurodevelopmental follow up, dyadic intervention and use of telemedicine allowing for a deeper understanding of the family adaptation that provide novel insight into long-term trajectory beyond discharge. Throughout care Patient P met criteria for both a traumatic stress disorder and global developmental delay. This case study highlights the threat complex care poses to neurodevelopment, pediatric mental health and family dynamics as well as opportunities for intervention.